China's Health Silk Road in the Middle East and North Africa amidst COVID-19 and a Contested World Order. Issue 135 (4th May 2022) - Zoubir, Yahia H.; Tran, Emilie
ABSTRACT: The COVID-19 pandemic has offered China a unique opportunity for worldwide deployment of its longstanding health diplomacy, renamed the Health Silk Road (HSR), now an integral part of its Belt and Road Initiative. As a self-proclaimed South-South collaborator and developer, 1 Beijing has assumed a leadership role, grounded in 'moral realism', in the world's health governance. Beijing's health diplomacy has received acclaim in the Middle East and North Africa (MENA). However, the pandemic has exacerbated preexisting tensions between China, the United States (US) and European Union (EU). Western countries, wary of China's rising power, reacted resentfully, confirming underlying systemic rivalry. This article argues that the currently disputed, or shifting, world order accounts for the diametrically opposed reactions between the West and the MENA toward China's Health Silk Road.